Using Using Batik in Sidomukti Village as an Etnopedagogical Learning Resource: Pemanfaatan Batik di Desa Sidomukti Sebagai Sumber Belajar Etnopedagogis - Wulan Wulan Nawangsari; Ari Metalin Ika Puspita; Nadi Suprapto (Elementary Teacher Education Program, Majalengka University, 2025)
Batik is one of the identities of the Indonesian nation. Batik is one of the common things in Indonesia related to one of the cultural diversity in Indonesia. The motifs in batik are closely related to life and Javanese culture which is quite strong. One of the Nusantara batik that is quite famous in East Java, specifically in Magetan Regency, is sidomukti batik. Sidomukti batik has quite a lot of its own motifs, each of which certainly has its own meaning and significance. It can be called sidomukti batik because this batik is made in the Sidomukti village area, this village is one of the villages in Magetan Regency that produces quite a lot of batik and of course many motifs have their own meaning and significance. Sidomukti Magetan batik has its own characteristics, namely batik with bamboo motifs. This existence of this research was conducted with the aim of utilizing sidomukti batik as a learning resource for ethnopedagogy. This study used a descriptive qualitative research design. After conducting the research, it can be concluded that sidomukti batik can be used as a learning resource for ethnopedagogy in elementary schools. Moreover, in a broader context, this research has illustrated how local art traditions can be transformed into innovative and sustainable learning media, which contribute to the achievement of SDG 4: quality education and preservation of Indonesian cultural heritage. Keywords: Batik, identity, learning resources, ethnopedagogy.